SWOT and PEST analysis in tourism management in Bintan Regency - Ady Muzwardi; Gulmok Simbolon (Indonesian Tourism Journal, 2024)
The Tourism Program Bintan Regency aims to develop and enhance the region's tourist attractions, destinations, and creative economy. The program focuses on developing and managing tourist attractions, monitoring and evaluating their management, and providing infrastructure and facilities. Marketing is also a crucial aspect, aiming to promote the region's attractions to domestic and international audiences. The SWOT and PEST analysis highlights Bintan Regency's strengths, including its natural attractions, rich cultural heritage, and friendly local community. However, it also identifies weaknesses, such as limited infrastructure, limited human resources, and limited marketing budget. The PEST analysis emphasizes the importance of considering multiple factors when analyzing the current situation of tourism in Bintan Regency. The Political factor influences the industry through government policies and regulations, while the Economic factor drives growth through investment and revenue generation. The Social factor contributes to sustainable tourism development through community engagement and participation, while the Technological factor increases accessibility and reach through mobile technology and online travel agencies. To overcome potential obstacles and challenges, such as limited infrastructure and amenities, competition from other destinations, climate change and environmental concerns, effective planning and management, and human resource development, Bintan Regency must leverage its strengths, address its weaknesses, consider external factors, and acknowledge potential challenges. By doing so, it can establish itself as a competitive tourist destination that attracts visitors from around the world.